2001
DOI: 10.1090/s0002-9947-01-02754-4
|View full text |Cite
|
Sign up to set email alerts
|

Ill-posedness for the derivative Schrödinger and generalized Benjamin-Ono equations

Abstract: Abstract. Ill-posedness is established for the initial value problem (IVP) associated to the derivative nonlinear Schrödinger equation for data in H s (R), s < 1/2. This result implies that best result concerning local well-posedness

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
129
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(134 citation statements)
references
References 21 publications
1
129
0
Order By: Relevance
“…There is a large literature on the Cauchy problem for (DNLS); see [38,39,19,20,36,3,8,9,42,43,15,11,16,23,24] and references therein. Here we are mainly interested in the results of energy space H 1 (R).…”
Section: Dnls and Mass Critical Nlsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a large literature on the Cauchy problem for (DNLS); see [38,39,19,20,36,3,8,9,42,43,15,11,16,23,24] and references therein. Here we are mainly interested in the results of energy space H 1 (R).…”
Section: Dnls and Mass Critical Nlsmentioning
confidence: 99%
“…This result is considered as a natural extension of 2π-mass condition for (DNLS). 3 From the following energy form…”
Section: Dnls and Mass Critical Nlsmentioning
confidence: 99%
“…On the other hand, Molinet, Saut, and Tzvetkov [Molinet et al 2001] proved that the flow map associated with BO, when it exists, fails to be C 2 in any Sobolev space H s ‫,)ޒ(‬ s ∈ ‫.ޒ‬ This result is based on the fact that the dispersive smoothing effects of the linear part of BO are not strong enough to control the low-high frequency interactions appearing in the nonlinearity of (1-1). It was improved by Koch and Tzvetkov [2005], who showed that the flow map fails even to be uniformly continuous in H s ‫)ޒ(‬ for s > 0 (see [Biagioni and Linares 2001] for the same result in the case s < − 1 2 ). As the consequence of those results, one cannot solve the Cauchy problem for the Benjamin-Ono equation by a Picard iterative method implemented on the integral equation associated with (1-1) for initial data in the Sobolev space H s ‫,)ޒ(‬ s ∈ ‫.ޒ‬ In particular, the methods introduced by Bourgain [1993b] and Kenig, Ponce, and Vega [Kenig et al 1993; for the Korteweg-de Vries equation do not apply directly to the Benjamin-Ono equation.…”
Section: Introductionmentioning
confidence: 97%
“…The Benjamin-Ono equation is one of the fundamental equations describing the evolution of weakly nonlinear internal long waves. It has been derived by Benjamin [1967] as an approximate model for long-crested unidirectional waves at the interface of a two-layer system of incompressible inviscid fluids, one being infinitely deep. In nondimensional variables, the initial value problem (IVP) associated with the Benjamin-Ono equation (BO) is…”
Section: Introductionmentioning
confidence: 99%
“…The first author [23,24] proved that (1) is small data global well-posed and scattering for s ≥ s c if m + d ≥ 4. Well-posedness of the Cauchy problem for (1) in d = 1 whose ∂(u m ) is replaced by ∂ x (|u| 2 u) is intensively studied by many authors (see, for example, [20,21,31,32,13,3,14,22,34,29] references therein). Presence of derivative causes some difficulties.…”
mentioning
confidence: 99%